Pengaruh Citra Merk dan Harga Terhadap Loyalitas Pelanggan pada Mie Gacoan Lippo - Yasin Yasin; Asih Susanti Putri; Wanda Nabilatuzzahro; Pupung Purnamasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study was to analyse the effect of brand image and price on customer loyalty of Mie Gacoan in Lippo. The method used was a questionnaire distributed to 100 respondents. The results of the analysis show that brand image is good for price and customer loyalty. This research recommends Mie Gacoan to maintain its brand image and consider an attractive pricing strategy.